Determinants and Strategies for Tourism Development at Gumumae Beach, Bula District, East Seram - Siti Hasanah Tuasikal; Leonard O. Kakisina; Yolanda M.T.N. Apituley (Publikasi Indonesia, 2024)
Gumumae Beach is one of the leading tourist destinations in East Seram Regency. The attraction is beach tourism characterized by brown sand and sloping and dominated by coastal vegetation in the form of coastal cassowaries and mangroves. The problem is the increase in the number of visitors only on certain holidays. The purpose of this research is to formulate a development strategy for Gumumae Beach Tourism. This study uses qualitative methods, data collected through interviews, field observations and documentation. Data analysis used multiple regression and SWOT. The regression results show that the cost of travel and the length of visit are inversely proportional to the frequency of visits. That is, the greater the travel cost and the longer the visit, the frequency of visits will decrease. SWOT analysis resulted in three prioritized tourism development strategies, namely: 1) optimize the potential of natural beauty, beaches and mangroves and improve culinary infrastructure and local culture through cooperation with the private sector; 2) develop environmentally friendly, clean and adaptive coastal tourism to the impacts of climate change; and 3) improve the knowledge and skills of human resources to serve visitors and increase the contribution of tourism to local revenue.